Scalar-Tensor Bianchi VI Models. (5th June 2013) - Belinchón, J. A.
Abstract : We study how may vary the gravitational and the cosmological "constants, " (G andΛ ) in several scalar-tensor theories with Bianchi III, V I 0, andV I h symmetries. By working under the hypothesis of self-similarity we find exact solutions for two different theoretical models, which are the Jordan-Brans-Dicke (JBD) withΛ ( ϕ ), and the usual JBD model with potentialU ( ϕ ) (that mimics the behaviour ofΛ ( ϕ ) ) . We compare both theoretical models, and some physical and geometrical properties of the solutions are also discussed putting special emphasis on the study of the isotropization of the solutions.